Holistic treatment as an alternative by nurses in oncologic pain control: experience report (Research, Society and Development, 2021)
Objective: This article aims to report the experience of nursing students on an educational action that addressed holistic and complementary treatments as an alternative for health professionals in the management and control of cancer pain. Methodology: This is a descriptive study, with a qualitative approach, of the experience report type, bringing the experience of nursing students from a university center in the metropolitan region of Belem do Pará when carrying out an educational action in the place of private oncological treatment in the municipality of Belem. Experience Report: In a conversation circle, a cloud of ideas was created based on the knowledge they had, then, through slides, the 4 types of holistic care were demonstrated: aromatherapy, music therapy, color therapy and acupuncture. When developing knowledge, a link was made available through SWAY, where professionals could consult the materials. Evidently, at this stage we used the active methodology in the form of a questionnaire, where several questions related to the subject were added on the Kahoot platform, the participating professionals should answer the questions true or false, thus accumulating points in the game. Final Considerations: The action taken made it possible to expand holistic knowledge about cancer pain from patients to interns and clinic professionals. Therefore, this work was able to describe the participation and elaboration of educational actions on the mentioned theme and concluding that nursing has autonomy to exercise its role in pain management, being able to use integrative and complementary practices.